Transcriptome Analysis on the Mechanism of Ethylicin Inhibiting Pseudomonas syringae pv. actinidiae on Kiwifruit - Tao Liu; Xiaoli Ren; Guangyun Cao; Xia Zhou; Linhong Jin (Microorganisms, 2021)
Bacterial canker disease caused by Pseudomonas syringae pv. actinidiae (Psa) is a devastating disease of kiwifruit, which is severely limiting the development of the kiwifruit industry. Ethylicin is a broad-spectrum plant biomimetic fungicide. However, its application in the control of kiwifruit bacterial canker is rarely reported, and the mechanism of ethylicin on Psa remains unknown. In this study, we investigated the effect of ethylicin on Psa in vitro and in vivo and found that ethylicin can inhibit the growth of Psa and prevent the cankering in the plant stem. Mechanism investigation indicated that ethylicin acted by limiting the movement of Psa, destroying the cell membrane of Psa, and inhibiting the formation of Psa biofilm. In addition, it was also found through transcriptomics research that ethylicin can up-regulate the expression of genes related to protein export and biofilm formation–Pseudomonas aeruginosa and down-regulate the expression of genes related to flagellar assembly in Psa. This study concluded that ethylicin can effectively inhibit Psa growth, and it could help to gain a better understanding of the mechanisms of ethylicin inhibiting Psa and provide practical data for the application of ethylicin as a highly potent agent for controlling the bacterial canker disease of kiwifruit.